Extended-time of Noninvasive Positive Pressure Ventilation Improves Tissue Perfusion after Coronary Artery Bypass Surgery: a Randomized Clinical Trial - Nasrala,Mara L. S. (2018)
Abstract Objective: To compare the effects of extended- versus short-time noninvasive positive pressure ventilation on pulmonary function, tissue perfusion, and clinical outcomes in the early postoperative period following coronary artery bypass surgery in patients with preserved left ventricular function. Methods: Patients were randomized into two groups according to noninvasive positive pressure ventilation intensity: short-time noninvasive positive pressure ventilation n=20 (S-NPPV) and extended-time noninvasive positive pressure ventilation n=21 (E-NPPV). S-NPPV was applied for 60 minutes during immediate postoperative period and 10 minutes, twice daily, from postoperative days 1-5. E-NPPV was performed for at least six hours during immediate postoperative period and 60 minutes, twice daily, from postoperative days 1-5. As a primary outcome, tissue perfusion was determined by central venous oxygen saturation and blood lactate level measured after anesthetic induction, immediately after extubation and following noninvasive positive pressure ventilation protocols. As a secondary outcome, pulmonary function tests were performed preoperatively and in the postoperative days 1, 3, and 5; clinical outcomes were recorded. Results: Significant drop in blood lactate levels and an improvement in central venous oxygen saturation values in the E-NPPV group were observed when compared with S-NPPV group after study protocol (P<0.01). The E-NPPV group presented higher preservation of postoperative pulmonary function as well as lower incidence of respiratory events and shorter postoperative hospital stay (P<0.05). Conclusion: Prophylactic E-NPPV administered in the early postoperative period of coronary artery bypass surgery resulted in greater improvements in tissue perfusion, pulmonary function and clinical outcomes than S-NPPV, in patients with preserved left ventricular function. Trial Registration: Brazilian Registry of Clinical trial - RBR7sqj78 - http://www.ensaiosclinicos.gov.br